Nationwide study of patients with head and neck paragangliomas carrying SDHB germline mutations. Issue 2 (6th February 2018) - Rijken, J. A.; Niemeijer, N. D.; Leemans, C. R.; Eijkelenkamp, K.; van der Horst‐Schrivers, A. N. A.; van Berkel, A.; Timmers, H. J. L. M.; Kunst, H. P. M.; Bisschop, P. H. L. T.; van Dooren, M. F.; Hes, F. J.; Jansen, J. C.; et al.
Abstract : Background: Germline mutations in the succinate dehydrogenase B ( SDHB ) gene predispose to hereditary paraganglioma (PGL) syndrome type 4. The aim of this study was to evaluate the clinical characteristics and outcome of treatment strategies for patients with head and neck paraganglioma (HNPGL) carrying SDHB germline mutations. Methods: This was a retrospective evaluation of patients with HNPGL carrying SDHB germline mutations in the Netherlands. Results: In a Dutch nationwide cohort study of SDHB germline mutation carriers, 54 patients with a total of 62 HNPGLs were identified. Forty‐one of 54 patients (76 per cent) visited the outpatient clinic because of associated complaints. Eight patients (15 per cent) had multiple PGLs. One patient (2 per cent) developed a phaeochromocytoma and three (6 per cent) developed a malignant PGL. Twenty‐seven patients (50 per cent) had an operation for their HNPGL and 15 (28 per cent) received radiotherapy. Three patients with HNPGL (6 per cent) were diagnosed with additional non‐paraganglionic tumours. Conclusion: If an SDHB germline mutation is identified in a patient with HNPGL, the clinician should be aware of the variable manifestations of the SDHB ‐linked tumour syndrome, the risk of catecholamine excess, concurrent phaeochromocytoma, and association with non‐paraganglionic tumours. Abstract : In a Dutch nationwide cohort study of SDHB germline mutation carriers, 54 patients with a total of 62 head and neck paragangliomas (HNPGLs) were identified. The clinician should be aware of the variable manifestations of the SDHB ‐linked tumour syndrome, the risk of catecholamine excess, concurrent phaeochromocytoma, and its association with non‐paraganglionic tumours. Contrary to previous reports on SDHB ‐linked tumours, the risk of developing metastatic SDHB ‐linked HNPGL seems relatively small. Multi‐disciplinary approach needed.